4G/5G low-cost wireless coverage scheme based on tapping the potential of existing networks - Dan YANG; Jing ZHANG; Peijin LV; Yun LU; Zhanchun YANG (Dianxin kexue)
Relevant research data shows that, the cost of China's 5G network deployment is expected to be about three times that of 4G.The network architecture, key technical principles and source hardware characteristics of the existing 4G and 5G networks were analyzed and studied.Three ideas for tapping the potential were proposed, which are using that how to use the old 4G resources in the construction of 5G networks, releasing 4G resources through 5G network deployment and maximizing use of 4G/5G sources, thereby reducing the investment cost and upgrade difficulty of the network.